Trends in Antibiotic Susceptibility Pattern of Community-acquired Uropathogens in the Nashik Division of Maharashtra - Dhangar, Dr. Sanjay P.; Gosavi, Dr. Amrapali D.; Gite, Dr. Sushant S. (SP’z Series New Insights on Urology and Urological Research Part II, 2023)
Background: Antibiotic resistance of urinary tract pathogens has increased worldwide. Knowledge of the antibiotic resistance patterns of uropathogens in specific geographical locations is an important factor for choosing an appropriate empirical antimicrobial treatment. The aim of this study is to provide information regarding local resistance patterns of urinary pathogens to the commonly used antibiotics in Nashik division of Maharashtra, India. Methodology: Urine samples collected and submitted to microbiology laboratories in Tambe hospital, Sangamner and SMBT IMSRC, Igatpuri, Nashik were identified by conventional methods over a period from August 2016 to March 2017. Antimicrobial resistance testing was performed by the standard technique in accordance with the recommendations of the Clinical and Laboratory Standards Institute. Results: Of the total 1575 mid-stream urine samples collected from suspected cases of urinary tract infection, 750 (47.61%) were positive for pathogenic bacteria. Escherichia coli (E. coli) was the most common isolate (68.8%) followed by Proteus spp. (13.7%), and Klebsiella spp. (7.46%). E. coli isolates were mostly susceptible to imipenem, meropenem (99.5%), followed by amikacin (92%), flouroquinolones (79-89%), nitrofurantoin (82%); however, only 69% of E. coli isolates were susceptible to trimethoprim-sulfamethoxazole and around 50% were susceptible to third generation cephalosporins. Conclusion: Nitrofurantoin and flouroquinolones may be considered as a first-line empiric antibacterial agent for urinary tract infections in outpatients in Nashik division of Maharashtra, India.